An Environment-Friendly Method for Green Synthesis of Pyranopyrazole Derivatives Catalyzed by CoCuFe2O4 Magnetic Nanocrystals under Solvent-Free Conditions. (31st December 2021) - Dadaei, Mahla; Naeimi, Hossein
Abstract: An efficient and rapid four component reaction of ethyl acetoacetate, hydrazine hydrate, malononitrile and different aldehydes at environmentally benign room temperature and solvent free conditions. This research has developed for synthesis of pyranopyrazole derivatives in the presence of CoCuFe2 O4 magnetic nanocrystals as reusable catalyst. The catalyst prepared and characterized by FT-IR, XRD, SEM, EDX and VSM techniques. The products confirmed by spectroscopic and physical data such as; melting points, FT-IR and 1 H NMR analyses.